209k views
2 votes
The solutions of the equations -x² + 4x +3 = 0 are

A. (x = -3) and (x = -1)
B. (x = 1) and (x = 3)
C. (x = -2 -√7) and (x = -2 + √7)
D. (x = 2 -√7) and (x = 2 + √7)

can someone explain this pls​

User Haseeb A
by
5.7k points

1 Answer

4 votes

Answer:

D. x = 2 − √7 and x = 2 + √7

Explanation:

-x² + 4x + 3 = 0

Multiply both sides by -1.

x² − 4x − 3 = 0

Factor using quadratic formula.

x = [ -b ± √(b² − 4ac) ] / 2a

x = [ -(-4) ± √((-4)² − 4(1)(-3)) ] / 2(1)

x = (4 ± √28) / 2

x = (4 ± 2√7) / 2

x = 2 ± √7

x = 2 − √7, 2 + √7

User Spkrtn
by
5.8k points